Selection of the Composition with High Glass Forming Ability in Zr-Cu-Ni-Al Bulk Metallic Glasses - Yajuan Sun (Advances in Materials Science and Engineering, 2014)
Three new Zr-Cu-Ni-Al bulk metallic glasses were developed through appropriate mixing of three binary eutectics Zr38.2Cu61.8, Zr51Al49, and Zr64Ni36. By suppressing solidification of competing crystalline phases, a new glass forming alloy Zr51Cu24.22Ni14.06Al10.72 with the critical diameter of up to 10 mm is obtained.